2020
DOI: 10.1186/s12877-020-01511-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between motoric cognitive risk syndrome and frailty among older Chinese adults

Abstract: Background: Motoric cognitive risk syndrome (MCR) is a newly proposed predementia syndrome incorporating subjective cognitive complaints and slow gait. Previous studies have reported that subjective cognitive complaints and slow gait are associated with frailty in cognitively unimpaired older adults, but little is known about the link between MCR and frailty in older adults. Therefore, the aim of the study was to explore the associations of MCR and its components with frailty in older Chinese adults. Methods: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 69 publications
0
18
1
Order By: Relevance
“…The prevalence of MCR in community-dwelling older adults ranged from 2% to 27% [30], which may be attributed to how MCR criteria are operationalized and how different populations were recruited in previous studies. In this study, the MCR prevalence was 10.4% at baseline, higher than in a previous study in 429 older adults aged 60 years and older admitted to a geriatric department in China [31] (4.0%). Our findings were similar to those of studies among community-dwelling Chinese elderly people (12.8% in men and 12.6% in women) [3] and in Mexican elderly people [32] (14.3%), which indicated that MCR might be more severe among the elderly living in the community.…”
Section: Discussioncontrasting
confidence: 79%
“…The prevalence of MCR in community-dwelling older adults ranged from 2% to 27% [30], which may be attributed to how MCR criteria are operationalized and how different populations were recruited in previous studies. In this study, the MCR prevalence was 10.4% at baseline, higher than in a previous study in 429 older adults aged 60 years and older admitted to a geriatric department in China [31] (4.0%). Our findings were similar to those of studies among community-dwelling Chinese elderly people (12.8% in men and 12.6% in women) [3] and in Mexican elderly people [32] (14.3%), which indicated that MCR might be more severe among the elderly living in the community.…”
Section: Discussioncontrasting
confidence: 79%
“…36 In contrast, a previous study suggested that subjective cognition was not associated with frailty syndrome. 37 The reason for this observation may be that the accuracy of self-reported cognitive complaints may be affected by many factors. Moreover, an interesting study con rmed that osteosarcopenia is often associated with the risks of falls or osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 99%
“…With MCR syndrome being a relatively new concept, prevalence rates have been complicated since no specific cognitive test has been identified for diagnosis and reported rates vary from 2% to 27% of populations worldwide 11. This may also be related to cultural differences across the globe in how and if people identify and report cognitive changes 11…”
Section: Subjective Memory Complaints Versus Normal Ageingmentioning
confidence: 99%